Influence of silicon doping on internal quantum efficiency and threshold of optically pumped deep UV AlGaN quantum well lasers. (26th November 2018) - Jeschke, J; Mogilatenko, A; Netzel, C; Zeimer, U; Weyers, M
Abstract: The influence of silicon doping on optically pumped AlGaN quantum well (QW) lasers has been analyzed. Either the QWs, quantum barriers, or the whole heterostructure were doped with Si concentrations between 6 × 10 16 and 1 × 10 19 cm −3 . When the QWs are doped up to 5 × 10 17 cm −3, laser threshold is reduced and internal quantum efficiency is increased most probably due to a reduction of group-III-vacancies during growth. Higher Si concentrations in the wells can increase the density of group-III-vacancies causing an increased laser threshold. High concentrations can also enhance band gap inhomogeneities and the free carrier density, which improves the internal quantum efficiency measured by photoluminescence. Doping of all layers with a Si concentration of 1 × 10 19 cm −3 deteriorates the QW quality, most probably because the silicon acts as an anti-surfactant reducing and delaying Ga incorporation.